Urinary Gluten Immunogenic Peptides Correlation with Celiac Disease: A Systematic Review - Prasetya, Alver; Yonatan, Eric Ricardo; Subagya, Jonathan Christianto; Tansil, Naomi Juwita; Lee, Yeong Yeh; Tenggara, Riki (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2024)
ABSTRACTBackground: Celiac disease (CD) is a condition caused by an abnormal immune response to gluten products. The mainstay of treatment is the gluten-free diet (GFD), but despite patients' efforts to avoid gluten products, some inevitably consume gluten. As current methods for monitoring are limited, a better marker is urgently needed. Urinary gluten immunogenic peptide (UGIP) has been shown to correlate with gluten intake and mucosal damage in CD patients. Therefore, the aim of this systematic review is to summarize the evidence on UGIP as a biomarker in CD patients.Method: This systematic review was conducted in accordance with the PRISMA statement guidelines. The literature search was done using PubMed, ProQuest, EBSCOHost, and Google Scholar for relevant journals published up to March 2023. Newcastle Ottawa Scale and Cochrane Risk of Bias were utilized in the quality assessment of the studies. Result: The literature search identified 85 studies. After eliminating irrelevant and duplicated studies, eight studies were included. Detectable UGIP concentration in the urine correlates with the degree of mucosal damage of CD patients (Marsh II-III). Although three observational studies concluded that there is a correlation between gluten intake and UGIP detection, two randomized controlled trials (RCTs) found that UGIP is not reliable for determining adherence to GFD. Furthermore, UGIP concentrations did not correlate with antibody titers and clinical symptoms. Conclusion:  UGIP may be a helpful biomarker for predicting the severity of mucosal damage in CD patients. However, further studies are needed to evaluate its role in predicting adherence to GFD.ABSTRAKLatar belakang: Penyakit Celiac (CD) adalah suatu kondisi yang disebabkan oleh respon imun yang tidak normal terhadap produk gluten. Pengobatan utama adalah dengan diet bebas gluten (GFD). Meskipun pasien berupaya untuk menghindari produk gluten, beberapa pasien dapat secara tidak sengaja mengkonsumsi gluten. Karena pemeriksaan untuk memantau konsumsi gluten masih terbatas, modalitas pemeriksaan yang dapat diandalkan sangat dibutuhkan. Beberapa bukti mengatakan terdapat korelasi antara peptida imunogenik gluten urin (UGIP) dengan asupan gluten serta kerusakan mukosa pada pasien CD. Oleh karena itu, tinjauan sistematis ini bertujuan untuk merangkum bukti tentang UGIP sebagai modalitas pemeriksaan pada pasien CD.Metode: Tinjauan sistematis ini dilakukan sesuai dengan pedoman pernyataan PRISMA. Pencarian literatur dilakukan menggunakan PubMed, ProQuest, EBSCOHost, dan Google Scholar untuk jurnal relevan yang diterbitkan hingga Maret 2023. Newcastle Ottawa Scale dan Cochrane Risk of Bias digunakan dalam penilaian kualitas studi.Hasil: Pencarian literatur mengidentifikasi 85 penelitian. Setelah mengeliminasi studi yang tidak relevan dan duplikat, delapan studi dimasukkan. Konsentrasi UGIP yang terdeteksi dalam urin berkorelasi dengan tingkat kerusakan mukosa pasien CD (Marsh II-III). Meskipun tiga studi observasi menyimpulkan bahwa ada korelasi antara asupan gluten dan deteksi UGIP, dua uji randomized controlled trials (RCT) menemukan bahwa UGIP tidak dapat diandalkan untuk menentukan kepatuhan terhadap GFD. Selain itu, konsentrasi UGIP tidak berkorelasi dengan titer antibodi dan gejala klinis. Kesimpulan: UGIP dapat dipertimbangkan untuk membantu untuk memprediksi tingkat keparahan kerusakan mukosa pada pasien CD. Namun, studi lebih lanjut diperlukan untuk mengevaluasi perannya dalam memprediksi kepatuhan terhadap GFD.